Characterization of a natural rubber nanocomposite reinforced with clay - Chirinos Collantes, Hugo David (2013)
This contribution shows the caracterization of nanocomposites from natural rubber latex reforcing by clay particles. The sortion, the mechanical and the thermical proporties were studied. In the sortion analysis, when increase the concentration clay the nanomaterial absorved low quantity of solvent. The mechanical properties analysis show a high hardness material when increase the clay but with low elasticity. The thermogravimetrical analysis shows low mass sold of nanomaterial by increasing clay concentration.